Metastatic Spinal Cord Compression and Steroid Treatment: A Systematic Review - Kumar, Abhishek; Weber, Michael H; Gokaslan, Ziya; Wolinsky, Jean-Paul; Schmidt, Meic; Rhines, Laurence; Fehlings, Michael G; Laufer, Ilya; Sciubba, Daniel M; Clarke, Michelle J; Sundaresan, Narayan; Verlaan, Jorrit-Jan; et al. (Clinical spine surgery, 2017)
Systematic review. We conducted a systematic review of the literature to answer the following questions regarding the use of steroid therapy in metastatic spinal cord compression (MSCC): 1. In cases of MSCC, what is the effect of steroid administration before definitive radiotherapy or surgery on ambulatory status, bowel and bladder function and survival? 2. What steroid dosing regimens are associated with the best outcomes concerning neurological symptoms and complication prevention in cases of MSCC? Currently, there is significant variation in the initial bolus dose, daily maintenance dose and duration of treatment when steroids are used as a bridge to definitive therapy for MSCC. A literature search following PRISMA guidelines was conducted in June 2016, using Medline via Ovid SP, Medline via PubMed, Embase, Biosis Previews and the Cochrane Library. Search terms used in each database varied slightly to optimize results. All generic steroid formulations were included along with spinal cord compression or myelopathy combined with metastatic or malignant tumors. Papers discussing acute traumatic causes of spinal cord compression were excluded, as were papers discussing cord compression from nonmetastatic tumors or epidural lipomatosis. Subjects were limited to adult humans undergoing definitive treatment with radiotherapy or surgery. Of the 309 papers retrieved, 66 full text studies were reviewed and 6 papers were found to address the stated questions. There is a paucity of high quality literature evaluating the use of steroids in MSCC. On the basis of the evidence available an initial 10 mg intravenous bolus of dexamethasone followed by 16 mg PO QD has been associated with fewer complications compared with 100 mg bolus and 96 mg QD. Weaning of steroids should occur rapidly after definitive treatment. Risk of gastric bleeding or perforation can be managed with the routine use of proton-pump inhibitors. Level IIIa.